PROSES MUTASI APARATUR PEMERINTAH DAERAH DI KABUPATEN KAPUAS HULU - Frisca Widyani E.42009042 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
Essay writing is intended to show and analyze the mutation process of local government officials in Kapuas Hulu. The title of this essay is based on issues raised in the mutation process is not based on the principle of the right man on the right place.This study uses a descriptive model of qualitative descriptive research. The research was carried out by four research steps, namely a preliminary investigation (pre-survey), making research plan (Research Proposal), making secondary data and primary data which is then analyzed on the same day after data collection in the field (interview or observasion), and a research report (skripsi). Research sites in Kapuas Hulu. Subjects Research is the Government of Kapuas Hulu associated with the mutation process, the Regional Employment Board Kapuas Hulu. The conclusion of this research is the process of mutation that occurs in Kapuas Hulu is not based on the principle of the right man on the right place, because the mutation that occurs during the process is still a lot of leads to the seniority system and spoil system, so it does not operate effectively and efficiently. Keyword: Mutation Process, Government Reform, The Right Man On The Right Place